1996
DOI: 10.1002/j.1460-2075.1996.tb01049.x
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila phosphoinositide 3-kinase Dp110 promotes cell growth.

Abstract: Phosphoinositide 3‐kinases (PI3Ks) have been identified in an evolutionarily diverse range of organisms, including mammals, Drosophila, yeast, plants and Dictyostelium. They are activated by a multitude of extracellular signals and implicated in mitogenesis, differentiation and cell survival, as well as in the control of the cytoskeleton and cell shape. Here we describe the molecular and functional analysis of Drosophila p110 (Dp110). A full‐length Dp110 cDNA was isolated and found to encode a protein homologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
356
0
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(381 citation statements)
references
References 56 publications
20
356
0
5
Order By: Relevance
“…In this screen, we identified PI3K RNAi and Akt RNAi as strong suppressors of the growth caused by Ras V12 , Dlg RNAi . PI3K and Akt are both components of the PI3K pathway (Leevers et al, 1996;Verdu et al, 1999;Weinkove et al, 1999;Scanga et al, 2000). Knockdown of either gene in an Ras V12 , Dlg RNAi background caused a complete suppression of the neoplastic growth and even caused a near-complete absence of mutant eye cells (Figures 1a-c and m).…”
Section: Resultsmentioning
confidence: 98%
“…In this screen, we identified PI3K RNAi and Akt RNAi as strong suppressors of the growth caused by Ras V12 , Dlg RNAi . PI3K and Akt are both components of the PI3K pathway (Leevers et al, 1996;Verdu et al, 1999;Weinkove et al, 1999;Scanga et al, 2000). Knockdown of either gene in an Ras V12 , Dlg RNAi background caused a complete suppression of the neoplastic growth and even caused a near-complete absence of mutant eye cells (Figures 1a-c and m).…”
Section: Resultsmentioning
confidence: 98%
“…This maternal role for Dakt1 prompted us to test for a potential role for PI3'K signaling in early Drosophila embryos. The ability of a dominant negative mutant of the catalytic subunit of Drosophila PI3'K (Dp110 D954A ) (Leevers et al, 1996) to a ect cell viability in early embyros was therefore tested. Expression of high levels of Dp110 D954 resulted in the extensive loss of cuticle ( Figure 1e) and a high incidence of DNA fragmentation as assayed by TUNEL staining (Figure 1f) indicative of apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…To assess this further, the ability of the catalytic subunit of PI3'K (Dp110) to directly activate D-Akt was analysed. For these experiments, cl-8 cell lines expressing wild-type Dp110 (WT Dp110) (Leevers et al, 1996) under the control of an inducible metallothionein (MT-1) promoter were used. Treatment of these cells with CuSO4 resulted in a 3 ± 5-fold increase in WT-Dp110 protein levels ( Loss of Dp110 activity in larval imaginal discs has been shown to result in the decrease of cell size and number (Leevers et al, 1996;Weinkove et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large amount of evidence supports a pivotal role for the phosphatidylinositol 3‐OH kinase (PI3K)/Akt/mTORC‐1 axis in the establishment of such a crosstalk. Studies showed that mutating several components of this signaling pathway influences both cell size and number, hence affecting organ size (Böhni et al, 1996; Leevers et al, 1996; Goberdhan et al, 1999). Likewise, inactivating mutations of genes leading to deregulated mTORC‐1 activity and failed metabolic checkpoints cause syndromes characterized by multiple, tumor‐like outgrowths in humans, such as Cowden syndrome (Liaw et al, 1997) and tuberous sclerosis (Brook‐Carter et al, 1994).…”
mentioning
confidence: 99%